Association between dietary inflammation index and frailty among community medical staff - Lu, Qinglian; Zong, Ming; Xu, Zhuo-Jun; Yu, Shanshan; Liu, Lang; Li, Yang; Wu, Yating; Zhao, Chunyan; Li, Hongxia (Frontiers in Nutrition, 2026)
ObjectiveTo investigate the relationship between the Dietary Inflammation Index (DII) and frailty among community medical staff.MethodsA stratified cluster sampling method was used to select community healthcare staff from Pudong New Area, Shanghai, between March and September 2024. Demographic characteristics were collected using a general information questionnaire. Dietary nutrient intakes were obtained via 24-hour dietary recall, and DII was calculated. Frailty status was assessed using the Fried Frailty Phenotype Scale. Logistic regression was performed to analyze the correlation between DII and frailty, and a restricted cubic spline model was used to explore the dose–response relationship.ResultsAmong 377 healthcare staff, 23 (6.1%) were frail, and 227 (60.2%) were pre-frail. The DII scores ranged from −4.02 to 3.73. The frail group had significantly higher DII scores than the pre-frail and non-frail groups, with statistical significance in DII quartile grouping. Logistic regression analysis showed that for each unit increase in DII absolute value, the risk of frailty increased approximately 3.4 times after adjusting for covariates (95% CI: 1.439 ~ 8.198, p = 0.005). The risk of frailty in the high DII group was 1.9 times that of the low DII group (95% CI: 1.152 ~ 3.190, p = 0.012). The restricted cubic spline model indicated a non-linear relationship between DII and frailty (p = 0.001).ConclusionFrailty among community healthcare medical staff is influenced by DII. Maintaining DII within a reasonable range may help prevent frailty.